PSYCHOLOGICAL CAPITAL AND OPTIMISM AS A PREDICTOR OF WORKPLACE HAPPINESS IN SERVICE-BASED INDUSTRIES IN INDIA (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
Working in multinational corporations (MNCs),  multicultural work environments present  obstacles. In today’s tumultuous workplace, it’s  more crucial than ever for businesses to ensure  that their employees are happy and productive.  This is because increasing production is  dependent on employee contentment. The  paper attempts to elucidate three critical factors  that affect an organization’s corporate culture.  The three factors that form the crux of the  argument are Psychological Capital, optimism,  and workplace happiness. The study was  conducted on 101 employees from the service  Industry. Both employee psychological capital  and optimism are significantly related to greater  work happiness within and across time. PsyCap  and Optimism are strongly correlated with  work place happiness. An employee who has  an optimistic mindset can see, understand, and  adapt things better as they can understand that  the new initiative might bring something positive  or modified. Conclusions and implications were  discussed for the findings, and limitations were  also discussed.
Keywords: Optimism; Psychological capital; workplace happiness; motivation